2020
DOI: 10.1055/a-1098-2101
|View full text |Cite
|
Sign up to set email alerts
|

Sustained colonoscopy quality improvement using a simple intervention bundle

Abstract: Background Unacceptable variation in colonoscopy quality exists. The Quality Improvement in Colonoscopy (QIC) study in 2011 improved quality by introducing an evidence-based “bundle” of measures into routine colonoscopy practice. The QIC bundle included: minimal cecal withdrawal time of ≥ 6 minutes; hyoscine butylbromide use; supine patient position for transverse colon examination; rectal retroflexion. Colonoscopy quality was measured by adenoma detection rate (ADR). The current study measured whether these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Endoscopy training improved the ADR 10 11 12 13 , mean number of adenomas per procedure (MAP) 14 , sessile serrated lesion (SSL) detection rate 15 , and proximal SP detection rate 16 . Lam et al reported that colonoscopy training improved interval CRC rates from 0.15 % to 0.08 % and early interval CRC rates from 0.07 % to 0.04 % 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopy training improved the ADR 10 11 12 13 , mean number of adenomas per procedure (MAP) 14 , sessile serrated lesion (SSL) detection rate 15 , and proximal SP detection rate 16 . Lam et al reported that colonoscopy training improved interval CRC rates from 0.15 % to 0.08 % and early interval CRC rates from 0.07 % to 0.04 % 17 .…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for sustained improvement in adenoma detection rate after implementation of a simple quality improvement bundle for colonoscopy, which persisted for several years after implementation, especially amongst the poorest performing endoscopists. 12 Despite the evident advantages of high-quality endoscopy reporting and use of a scoring system in UC, there is a relative paucity of studies designed to investigate reporting quality and use of endoscopic indices in clinical practice. To address this, we conducted a multicentre study, carried out over two phases, that aimed to assess baseline reporting quality and evaluate the impact of a set of interventions (a bundle) designed at standardising and optimising reporting.…”
Section: Introductionmentioning
confidence: 99%
“…A “bundle” in this context offers a structured way of improving healthcare processes and involves a small, straightforward set of practices (generally three to five) that, when performed collectively and reliably, can improve outcomes. There is evidence for sustained improvement in adenoma detection rate after implementation of a simple quality improvement bundle for colonoscopy, which persisted for several years after implementation, especially amongst the poorest performing endoscopists 12 …”
Section: Introductionmentioning
confidence: 99%
“…Feedback with quality assurance data has been shown to modify ADR and the associated PCCR rates, but this is challenging to deliver at scale 3 . More straightforward educational interventions “evidence bundles” can also improve ADR with durable effects especially for poor performers 4 . Devices can also modify ADR, such as wider‐angle instruments, advanced endoscopic imaging, or caps and cuffs, though there are no data yet that this links to reduced PCCRC 5 …”
mentioning
confidence: 99%